Jamming the Classroom : Musical Improvisation and Pedagogical Practice - Heble, Ajay, 1961-; Stewart, Jesse, 1974- (Book collections on Project MUSE., 2023)
Drawing on original interviews with improvising musicians, on critical pedagogy and cultural studies, and on the authors' personal histories with improvised music as a form of activism, community-based pedagogy, Jamming the Classroom examines how the teaching and learning of improvisational musical practices can be understood as vital and publicly resonant acts that generate new forms of knowledge, new understandings of identity and community, and new imaginative possibilities. The book takes its cue not just from the learning in conventional classrooms and credentialing institutions but also from the work that happens in and through broader communities of practice. Heble and Stewart ask how the improvisational practices of artists and the internal educational endeavors within community groups model--and enact--new forms of community-making and critical thinking, as well as what it means to theorize the pedagogy of improvised music in relation to public programs of action, debate, and critical practice and the context of material practices and struggles for institutional authority.